Adding a Dimension to the Dichotomy: Affective Processes Are Implicated in the Relationship Between Autistic and Schizotypal Traits - Larson, Felicity V.; Wagner, Adam P.; Chisholm, Katharine; Reniers, Renate L. E. P.; Wood, Stephen J. (Frontiers in Psychiatry, 2020)
Introduction: There is a recognised increase in vulnerability to psychosis in autistic people (AP). However, the construct of psychosis (particularly schizophrenia) contains several distinct factors, making understanding the relationship between autism and psychosis complex. Previous research has suggested that affective lability may be particularly related to psychotic experiences for AP who have experienced psychosis (AP-P). There is also a suggestion that psychosis might be a state of extreme (over)empathising, perhaps related to emotional processes. Method: We recruited three groups: AP-P (N=23), a group of AP who had not experienced psychosis (AP-NP; N=59) and a neurotypical group (N=41). Participants completed measures of autistic traits, schizotypal traits (as a proxy for psychosis-proneness), emotional processes, and perspective taking (as a proxy for the type of empathising most theoretically likely to be linked to psychosis). As well as comparisons between groups, regression analyses were used to understand the influence of dependent variables on schizotypal traits. Results: We found that AP-P had significantly higher rates of schizotypy (positive and disorganised), as well as higher rates of emotional difficulties. Across all groups, affective lability had a positive and significant association with positive and disorganised schizotypal traits. Differences in perspective taking between groups were small and generally non-significant, particularly in adjusted comparisons; additionally, its impact on schizotypy was small and non-significant. Discussion: Our findings suggest that positive and disorganised schizotypy, in particular, have a relationship with affective lability. This, in turn, supports the idea of emotional processes as related to the development of schizotypal traits and psychosis across all individuals, regardless of autism diagnostic status. We found no evidence of empathy relating to any subscale of schizotypy, or the total schizotypy score. We contend that emotional processes should be considered in exploration of the relationship between autism and schizotypy in future. This may help to explain some of the findings of overlap between these constructs in previous research. Factors known to affect neurodevelopment of emotion systems such as history of early trauma, challenges during pregnancy and birth, and early childhood experiences of adversity during critical windows of development need further consideration in future research.